2006
DOI: 10.1111/j.1440-1681.2006.04380.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluvastatin Increases Heterotopically Induced Ossicles in Mice

Abstract: 1. The aim of the present study was to evaluate the influence of fluvastatin (3-hydroxy-3-methylglutarylcoenzyme A reductase inhibitor) on heterotopic ossification (HO) induced by HeLa cells. 2. C57Bl/6 mice were injected with 3 x 10(6) HeLa cells into right thigh muscles. Mice in the experimental group received fluvastatin 1.2 mg/kg per day for 17 consecutive days, while mice in the control group received placebo. Intact mice served as an additional control. Seventeen days post-HeLa cell grafting, blood sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Hence, not systemic but rather topical application of statin, with bioerodible carrier such as propylene glycol alginate (29) or gelatine hydrogel (30), seems to be an appropriate strategy for osteogenesis. In fact, several studies have revealed the effectiveness of locally applied statin for osteogenesis (7–10, 29). However, before the anabolic effect of locally applied statin can be introduced to implant dentistry, further studies into the carrier are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, not systemic but rather topical application of statin, with bioerodible carrier such as propylene glycol alginate (29) or gelatine hydrogel (30), seems to be an appropriate strategy for osteogenesis. In fact, several studies have revealed the effectiveness of locally applied statin for osteogenesis (7–10, 29). However, before the anabolic effect of locally applied statin can be introduced to implant dentistry, further studies into the carrier are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, local application of statin with an absorbable collagen sponge can enhance the bone healing of surgically created bone defects (7). Several studies have elucidated the relationship between locally applied statin and osteogenesis (8–10).…”
Section: Introductionmentioning
confidence: 99%
“…by increasing expression of bone morphogenetic protein-2 (BMP-2), which leads to osteoblast differentiation and bone formation [1,2]. Administration of statins may also affect heterotopic ossification [3]. BMP-2 treatment of neural crest cells increases melanogenesis by promoting the synthesis of melanin [4].…”
Section: Introductionmentioning
confidence: 99%
“…No typical finding of inflammation or other adverse symptoms observed in this study indicated that the dose of statin used here (2.4 mg/kg) was in the normal range for bone formation. In previous studies, the concentration of FS ranged from 1.2–3.6 mg/kg, when applied topically to successfully enhance bone metabolism in mice [ 57 , 58 ]. The systemic bioavailability of FS is low, due to the first-pass effect at the intestinal and/or hepatic level [ 59 ].…”
Section: Discussionmentioning
confidence: 99%